2022
DOI: 10.1177/08903344221138101
|View full text |Cite
|
Sign up to set email alerts
|

“Don’t Feel Like You Have to Do This All on Your Own”: Exploring Perceived Partner Support of Breastfeeding Among Black Women in Kentucky

Abstract: Background: Few researchers have explored partner breastfeeding support among Black women, who report low breastfeeding rates compared to women of other cultural groups. Ways to encourage partner support of Black women’s breastfeeding can be understood from an Afrocentric perspective. Research Aim: To explore perceptions of partner support among Black mothers to develop a culturally relevant framework of partner breastfeeding support. Methods: Secondary data analyses of qualitative data from a larger prospecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…For example, one systematic review found little evidence for an association between exclusive breastfeeding and receiving social support from friends and family 56 . However, qualitative research has revealed social support from partners/spouses was critical for women to meet their breastfeeding goals and lack of support impeded women from meeting their breastfeeding goals 57,58 . In terms of mental health, previous research has established that social support from partners, family members, and friends are protective factors against the development of adverse mental health outcomes among working mothers 44,45,59,60 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, one systematic review found little evidence for an association between exclusive breastfeeding and receiving social support from friends and family 56 . However, qualitative research has revealed social support from partners/spouses was critical for women to meet their breastfeeding goals and lack of support impeded women from meeting their breastfeeding goals 57,58 . In terms of mental health, previous research has established that social support from partners, family members, and friends are protective factors against the development of adverse mental health outcomes among working mothers 44,45,59,60 .…”
Section: Discussionmentioning
confidence: 99%
“…56 However, qualitative research has revealed social support from partners/spouses was critical for women to meet their breastfeeding goals and lack of support impeded women from meeting their breastfeeding goals. 57,58 In terms of mental health, previous research has established that social support from partners, family members, and friends are protective factors against the development of adverse mental health outcomes among working mothers. 44,45,59,60 However, more research is needed to understand the relationships between social support and work-family conflict.…”
Section: Discussionmentioning
confidence: 99%
“…or convenience (e.g., Item 6 "Formula-feeding is the better choice if the mother plans to work outside the home"), and thus the removed items may contribute less to a homogeneous construct. Moreover, we assume that Item 11 may be more closely related to social norms or support, which alongside attitudes towards breastfeeding in uence breastfeeding behavior and duration (52).…”
Section: Criterion Validitymentioning
confidence: 99%